Higher Serum Levels of Lactate Dehydrogenase Before Microsurgery Predict Poor Outcome of Aneurysmal Subarachnoid Hemorrhage - Zheng, Shufa; Wang, Haojie; Chen, Guorong; Shangguan, Huangcheng; Yu, Lianghong; Lin, Zhangya; Lin, Yuanxiang; Yao, Peisen; Kang, Dezhi (Frontiers in Neurology, 2021)
Introduction: We explored whether higher preoperative serum levels of lactate dehydrogenase (LDH) predicted outcome 3 months after surgery in patients with aneurysmal subarachnoid hemorrhage (aSAH) treated using microsurgical clipping in our institution. Methods: Patients with aSAH treated at our institution between 2010 and 2018 were enrolled. The following parameters were recorded: age, sex, smoking and drinking history, medical history, Hunt–Hess and Fisher grades, aneurysm location, aneurysm size, surgical treatment, delayed cerebral ischemia (DCI), intracranial infection, hydrocephalus, pneumonia, and preoperative serum LDH levels within 24 h of aSAH. We investigated whether preoperative serum LDH levels were associated with Hunt–Hess grade, Fisher grade, and functional neurological outcome. Results: In total, 2,054 patients with aSAH were enrolled, 874 of whom were treated using microsurgical clipping. The average serum LDH level (U/L) was significantly lower in the good outcome group (180.096 ± 50.237) than in the poor outcome group (227.554 ± 83.002; p < 0.001). After propensity score matching, the average serum LDH level (U/L) was still lower in the good outcome group (205.356 ± 76.785) than in the poor outcome group (227.119 ± 86.469; p = 0.029). The area under the receiver operating characteristic (ROC) curve was 0.702 (95% confidence interval [CI]: 0.650–0.754; p < 0.001). Based on the ROC curve, the optimal cutoff value for serum LDH levels as a predictor of poor 3-month outcome (modified Rankin Scale score > 2) was 201.5 U/L. The results revealed that Hunt–Hess grade, Fisher grade, DCI, pneumonia, and serum LDH (>201.5 U/L) were significantly associated with poor outcome. After propensity score matching, serum LDH levels > 201.5 U/L were still considered an independent risk factor for poor outcome (odds ratio: 2.426, 95% CI = 1.378–4.271, p = 0.002). Serum LDH levels were associated with Hunt–Hess and Fisher grades and were correlated with functional neurological outcomes (p < 0.001). Conclusions: Our findings showed that higher preoperative serum levels of LDH correlated with Hunt–Hess grade, Fisher grade, and neurological functional outcome, and predicted the outcome of aSAH treated by microsurgical clipping at 3 months, which was involved in the related mechanisms of early brain injury and showed its potential clinical significance in patients with aSAH.